Friday, 15 June 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.3904
|View full text |Cite
|
Sign up to set email alerts
|

OP0305 Disease interception in psoriasis patients with subclinical joint inflammation by interleukin 17 inhibition with secukinumab – data from a prospective open label study

Abstract: BackgroundMusculoskeletal changes precede the onset of psoriatic arthritis (PsA). A subset of psoriasis patients is characterised by arthralgia as well as inflammatory changes in the joints visible by MRI assessment. These patients have a high risk to progress into PsA.ObjectivesTo test the concept of a very early intervention in PsA we exposed psoriasis patients with subclinical joint inflammation to the anti-interleukin (IL)−17A antibody secukinumab. We hypothesised that IL-17A inhibition disrupted the early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to evaluate the alteration in sonographic features of subclinical enthesitis with an IL‐12/IL‐23p40 inhibitor and the first study to investigate sonographic treatment responses in patients with asymptomatic psoriasis who are naive to systemic therapy. However, a recent study demonstrated that downstream inhibition of IL‐17 may have a similar effect on subclinical PsA ().…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to evaluate the alteration in sonographic features of subclinical enthesitis with an IL‐12/IL‐23p40 inhibitor and the first study to investigate sonographic treatment responses in patients with asymptomatic psoriasis who are naive to systemic therapy. However, a recent study demonstrated that downstream inhibition of IL‐17 may have a similar effect on subclinical PsA ().…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that psoriasis patients who will develop PsA soon after diagnosis of psoriasis could be identified by unspecific arthritic symptoms and should therefore receive rheumatological care. Recent evidence suggests that early intervention treatment of PsA with biologic disease-modifying anti-rheumatic drugs (DMARDs) halts the progression of bone changes and decreases synovial inflammation [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of disease interception was recently introduced (92). One hypothesis considers the possibility of arresting progression of psoriasis to PsA by targeting cytokines common to the pathogenesis of both diseases.…”
Section: Expert Commentary: Dermatologists Are Important In Treating the Spectrum Of Psoriatic Diseasementioning
confidence: 99%
“…One recent cohort study found that systemic therapies for psoriasis may indeed reduce the incidence of PsA progression-especially the manifestation of dactylitis-compared with topical therapies among patients with psoriasis (93). In the Interception in Very Early PsA (IVEPSA) study, the anti-IL-17A antibody secukinumab arrested the progression of joint symptoms in patients with psoriasis, subclinical inflammatory changes, and arthralgia (92,94). Suppression of the IL-23/IL-17 axis with the IL-12/23 inhibitor ustekinumab reduced subclinical enthesopathy from 12 to !52 weeks of treatment in patients with moderate to severe psoriasis who had !1 entheseal change detected by ultrasonography and no diagnosis of PsA (95).…”
Section: Expert Commentary: Dermatologists Are Important In Treating the Spectrum Of Psoriatic Diseasementioning
confidence: 99%